2020
DOI: 10.3390/v12080869
|View full text |Cite
|
Sign up to set email alerts
|

The Minor Matrix Protein VP24 from Ebola Virus Lacks Direct Lipid-Binding Properties

Abstract: Viral protein 24 (VP24) from Ebola virus (EBOV) was first recognized as a minor matrix protein that associates with cellular membranes. However, more recent studies shed light on its roles in inhibiting viral genome transcription and replication, facilitating nucleocapsid assembly and transport, and interfering with immune responses in host cells through downregulation of interferon (IFN)-activated genes. Thus, whether VP24 is a peripheral protein with lipid-binding ability for matrix layer recruitment has not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…VP24 is also known as the minor viral matrix protein as it can be associated with cellular membranes [ 23 ]. However, a recent publication observed that EBOV VP24 does not associate with lipids, so its presence on the viral matrix layer likely does not depend on direct lipid interactions [ 68 ].…”
Section: Ebola Virus: From a Virology Point Of Viewmentioning
confidence: 99%
“…VP24 is also known as the minor viral matrix protein as it can be associated with cellular membranes [ 23 ]. However, a recent publication observed that EBOV VP24 does not associate with lipids, so its presence on the viral matrix layer likely does not depend on direct lipid interactions [ 68 ].…”
Section: Ebola Virus: From a Virology Point Of Viewmentioning
confidence: 99%
“…VP24 was originally described as a minor matrix protein based on its presence in viral particles and the apparent capacity of VP24 from EBOV or MARV to associate with cellular membranes [7][8][9]. However, VP24 lacks measurable capacity to directly bind lipids [10]. Rather, VP24 interacts with NP and VP35 to promote formation of nucleocapsid-like structures (NCLS) nearly identical to the mature nucleocapsids found in virions [11].…”
Section: Introductionmentioning
confidence: 99%